Mondo family proteins in diabetes - Barodia, Sandeep Kumar; Grant, Maria B.; Gorbatyuk, Marina S. (Frontiers in Endocrinology, 2026)
Carbohydrate-responsive element binding protein (ChREBP) and Max-like protein X (MLX) are key Mondo Family Proteins (MFPs) acting as transcription factors. They are known to couple intracellular sugar levels with carbohydrate and lipid metabolism by regulating glucose-responsive gene expression. MondoA regulates lipid metabolism and insulin signaling in addition to controlling glucose uptake, whereas ChREBP primarily regulates de novo lipogenesis and glycolysis. Differential gene expression data suggest that the expression of MondoA and ChREBP is cell type-specific, which is an important consideration when designing therapeutic strategies to control MFP-regulated transcriptional programs for different tissue-specific systems. In this review, we summarize recent advances made in the research field studying diabetes and its multi-organ complications, including those affecting the kidney, liver, heart, and retina. We also discuss recent advances in MFP-targeted therapies.